PENGARUH INSENTIF DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT ASIA KARET - Shandy Gunawan; Nicholas Tanuwijaya; Octavia Paulus; Linda Linda (Jurnal Darma Agung, 2019)
The researcher took the object of research from PT. Asia Karet, the selection of objects is caused by a decrease in employee performance Employee performance is the result of work that becomes a benchmark for employees. Employee performance is influenced by several factors including communication and incentives. Communication within the company must run well both vertically and horizontally to reduce misinformation in working both orders from superiors or information between coworkers. Communication has an important role in efforts to achieve organizational goals, so it can be said that the success or failure of an organization is largely determined by the quality of communication possessed by people in the organization concerned. The population used was 67 people with sampling using saturated sampling and 30 employees to test validity taken from other companies. The research method used is a quantitative approach, a type of quantitative descriptive research. Methods of collecting data with interviews, questionnaires and documentation studies. The analytical method used is multiple linear regression, simultaneous coefficient of determination and testing (F-Test) with Fcount> Ftable (40,934> 3,080) and partially (Test-t) with the value for incentive variable t count> t table (3,037> 1,981) and communication ((2,932> 1,981). The results of the study show that incentives and communication simultaneously and partially have a positive and significant effect on the performance of employees at PT. Asia Karet